The Transmission of Herbal Medicine to China via the Silk Road in Medieval Ages - Ali Mollahassani; Aoyu CHENG; Weidong ZHANG; Ye WU; Jin LU (Chinese Medicine and Culture)
Abstract. The Silk Road has long been recognized as a vital channel for cultural and intellectual exchange, profoundly influencing the cosmopolitan identity of Tang emperor’s culture. Beyond the trade of goods like tea, silk, and carpets, this network also fostered the transfer of medical knowledge. Traditional Chinese medicine (TCM), with its extensive pharmacopoeia of over ten thousand herbal medicines, benefited significantly from exchanges with neighboring countries and regions. This review explores the intricate connections between TCM and other medical systems facilitated by the Silk Road, highlighting representative herbs introduced from regions along the route. It underscores the reciprocal influences that shaped medical practices in both Eastern and Western traditions, offering insights into the potential integration of traditional and modern biomedical approaches today.